Comparison Of Apple Puree Usage On The Physical Quality And Sensory Quality Of Steamed Sponge Cake - Rachel Audina Nur’azzura Putri; Annis Kandriasari; Alvina Fadila Maulida (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to analyze the comparison of apple puree usage on the physical quality and sensory quality of steamed sponge cake. Steamed sponge cake generally uses eggs as a binding, leavening, and texture-forming agent, although local apples containing pectin have the potential to be used as a substitute for part of the eggs. The research method used was an experimental method with three formulations of apple puree usage at 30%, 40%, and 50% of the total egg used. Physical quality testing was carried out on the expansion ability and cracking ability, analyzed using the One-Way Anova Completely Randomized Design (CRD) test followed by Duncan's test. Sensory quality testing was conducted by 45 semi-trained panelists on the aspects of shape, aroma, taste, and texture, analyzed using the Kruskal-Wallis test. The results showed that the highest expansion ability was obtained in the 40% treatment with an average of 136.7%, while the highest cracking ability was obtained in the 50% treatment with an average of 106.31%. The Anova test results showed no significant effect of apple puree usage on expansion ability, but a significant effect on cracking ability. The Kruskal-Wallis test results showed no significant effect of apple puree usage on shape, cinnamon aroma, sweetness, apple taste, and texture, except for apple aroma, which showed a significant effect. Overall, the treatment with 30% apple puree gave the best results in shape, sweetness, and texture, so this formula is recommended for optimizing the utilization of apple puree as a local food ingredient in steamed sponge cake products.